The Intro Course: A Pedagogical Toolkit - Jocelyn Thorpe; Sonja Boon; Lisa Bednar; Rachel Hurst; Krista Johnston; Heather Latimer; Marie Lovrod; Carla Rice; Alissa Trotz (Atlantis)
Abstract This article offers ideas and strategies for teaching introductory-level courses in Gender and Women’s Studies by providing the responses of eleven experienced educators who were asked two questions: What main theme or idea do you hope students will learn in the introductory class you teach? And what practical strategies do you use in the classroom to achieve that learning objective?